1978
DOI: 10.1007/bf01966600
|View full text |Cite
|
Sign up to set email alerts
|

The Schultz-Dale reaction: A review

Abstract: Vascular (pulmonary and hepatic blood vessels) and nonvascular (gastro-intestinal, reproductive and respiratory systems) smooth muscle preparations obtained from specifically sensitized animals of numerous species including man contract to specific antigen in vitro (Schultz-Dale phenomenon). This immunopharmacological technique is a useful tool to demonstrate immediate-type hypersensitivity in actively or passively sensitized tissues and may be used to investigate the nature of the principal pharmacological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 98 publications
1
49
0
Order By: Relevance
“…These results suggested that mast cell-derived renin triggers the local formation of ANG II, which then acts on AT 1 R on bronchial smooth muscle eliciting contraction. We then compared the bronchial contractile response to ANG II to that of methacholine, a prototypical bronchoconstricting agent [positive control (17,18)] and histamine, another bronchoconstricting agent (17), to which the rat is insensitive [negative control (19,20)]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that mast cell-derived renin triggers the local formation of ANG II, which then acts on AT 1 R on bronchial smooth muscle eliciting contraction. We then compared the bronchial contractile response to ANG II to that of methacholine, a prototypical bronchoconstricting agent [positive control (17,18)] and histamine, another bronchoconstricting agent (17), to which the rat is insensitive [negative control (19,20)]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Schultz-Dale reaction (Schultz, 1910;Dale, 1913;Chand & Eyre, 1978) has been used extensively to study anaphylactic contraction of airway tissue preparations such as the trachea, bronchi and lung parenchymal strips. Cumulative evidence showed that peptidoleukotrienes and histamine are the two major mast cell-derived mediators responsible for the anaphylactic contraction of the airways from both human and guinea-pig (Bjorck & Dahlen, 1993;Jonsson & Dahlen, 1994;Roquet et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Antigen-induced contraction of isolated trachealis from actively or passively sensitized guinea-pigs has been used by many investigators as a model of immediate hypersensitivity (Chand & Eyre, 1978;Adams & Lichtenstein, 1979;Hand & Buckner, 1979;Burka & Paterson, 1980;1981ab). Similarly, contraction to antigen can be elicited in passively (Dunlop & Smith, 1975;Dunlop et al, 1977;Adams & Lichtenstein, 1979;Davis et al, 1982) and intrinsically sensitized human tracheobronchial smooth muscle (Davis et al, 1982;Dahlen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%